2015
DOI: 10.1176/appi.focus.130211
|View full text |Cite
|
Sign up to set email alerts
|

Obsessive-Compulsive Disorder: Diagnosis, Epidemiology, Etiology, and Treatment

Abstract: Obsessive-compulsive disorder (OCD) has been given increased attention in DSM-5, receiving its own chapter. In this article, the authors discuss changes to the diagnostic criteria and symptoms differentiating OCD from other disorders. Two new specifiers, which have relevance in regard to treatment selection, appear in DSM-5: level of insight and presence of tic disorder. The epidemiology of OCD remains under investigation and may be modified based on the new DSM-5 criteria. Current data regarding age of onset … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 180 publications
0
5
0
Order By: Relevance
“…Obsessive-compulsive disorder (OCD) was originally believed to be a rare mental illness. However, recent surveys and research have shown that OCD is one of the most common mental disorders (Sassano-Higgins & Pato, 2015). The study's results…”
Section: Introductionmentioning
confidence: 79%
“…Obsessive-compulsive disorder (OCD) was originally believed to be a rare mental illness. However, recent surveys and research have shown that OCD is one of the most common mental disorders (Sassano-Higgins & Pato, 2015). The study's results…”
Section: Introductionmentioning
confidence: 79%
“…Obsessive-Compulsive Disorder (OCD) is a very debilitating psychological disorder characterized by the presence of unwanted, disturbing thoughts and anxiety or repetitive behaviors causing distress and explicit disorder. [ 1 ] The lifetime prevalence of OCD is approximately 2%,[ 2 ] and its prevalence in Iran is reported to be 21.57%. [ 3 ] Due to OCD's clinical features, the patients' families often change their daily activities in response to symptoms, in an attempt to relieve anxiety and/or reduce the time spent in the rituals.…”
Section: Introductionmentioning
confidence: 99%
“…Obsessive-compulsive disorder (OCD) is a heterogeneous neuropsychiatric condition that affects 3% of the population worldwide13 and ~1.8% in Iran 4. Overall, the prevalence of OCD is slightly more in women than men with an earlier onset in the male patients 5…”
Section: Introductionmentioning
confidence: 99%